2017
DOI: 10.1002/nau.23299
|View full text |Cite
|
Sign up to set email alerts
|

Results of an innovative bulking agent in patients with stress urinary incontinence who are not optimal candidates for mid‐urethral sling surgery

Abstract: PBI with PDMS-U is a viable treatment option in women with a relative contra-indication for mid-urethral sling surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…From 2011, multiple hospitals have included PDMS‐U a standard treatment option for patients with SUI or mixed urinary incontinence (MUI). Objective and subjective success rates at 6 to 12 months follow‐up varied from 59% to 89% and 35% to 90%, respectively 8‐10 . At 2 years follow‐up, objective cure rates of 33% to 66% were reported 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…From 2011, multiple hospitals have included PDMS‐U a standard treatment option for patients with SUI or mixed urinary incontinence (MUI). Objective and subjective success rates at 6 to 12 months follow‐up varied from 59% to 89% and 35% to 90%, respectively 8‐10 . At 2 years follow‐up, objective cure rates of 33% to 66% were reported 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…It's unique feature is that it polymerizes in situ into a uniform elastomer, remaining flexible and adapting itself to the environment. This is thought to reduce the risk of migration . In a clinical trial in the Netherlands, 76‐88% of the patients showed subjective improvement at 12‐25 months follow‐up …”
Section: Resultsmentioning
confidence: 99%
“…This is thought to reduce the risk of migration. 38,39 In a clinical trial in the Netherlands, 76-88% of the patients showed subjective improvement at 12-25 months follow-up. 40 In conclusion, although, there have been a number of studies conducted to look at the short-term efficacy, durability and safety of UBAs, in order to guide future practice, further comparative randomised trials involving a placebo or conservative treatment arm are required with long-term follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials comparing UBA with MUS surgery are needed to determine if UBA treatment achieves cure rates of 79% or higher. Cohort studies of bulking agent Urolastic report results lower to this threshold with subjective and objective cure rates of 56% to 68% and 59% to 65%, respectively, after 6‐ and 12‐month follow‐up . A systematic review of other bulking agents show on the other hand subjective and objective success rates up to 89% and 73% …”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies of bulking agent Urolastic report results lower to this threshold with subjective and objective cure rates of 56% to 68% and 59% to 65%, respectively, after 6-and 12-month follow-up. 4,7,24 A systematic review of other bulking agents show on the other hand subjective and objective success rates up to 89% and 73%. 8 There is no worldwide consensus about the exact place of UBA in current treatment protocols.…”
Section: Discussionmentioning
confidence: 99%